2023
DOI: 10.1017/s1047951123000240
|View full text |Cite
|
Sign up to set email alerts
|

Serum-soluble suppression of tumourigenicity-2 as a biomarker in children with congestive heart failure

Abstract: Background: We aimed to evaluate serum soluble suppression of tumorigenicity-2 in children with congestive heart failure, to assess the diagnostic and prognostic values of soluble suppression of tumorigenicity-2 in these patients, and to correlate its levels with various clinical and echocardiographic data. Methods: We included 60 children with congestive heart failure as the patient group. Sixty healthy children of matched age and sex served as the control group. Patients were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a previous study, Amer, Eslam et al included 60 children with congestive heart failure as a patient group and sixty age- and sex-matched healthy children as a control group. The results showed that sST2 is a good diagnostic and predictive biomarker for children with congestive heart failure ( 30 ). As a traditional cardiac biomarker, NT-proBNP has been extensively reported to be significantly elevated in patients with myocarditis or animal models of myocarditis and is a risk factor for poor prognosis in children with fulminant myocarditis ( 31 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Amer, Eslam et al included 60 children with congestive heart failure as a patient group and sixty age- and sex-matched healthy children as a control group. The results showed that sST2 is a good diagnostic and predictive biomarker for children with congestive heart failure ( 30 ). As a traditional cardiac biomarker, NT-proBNP has been extensively reported to be significantly elevated in patients with myocarditis or animal models of myocarditis and is a risk factor for poor prognosis in children with fulminant myocarditis ( 31 34 ).…”
Section: Discussionmentioning
confidence: 99%